Exercise training reverses cardiac aging phenotypes associated with heart failure with preserved ejection fraction in male mice. Issue 6 (22nd May 2020) - Roh, Jason D.; Houstis, Nicholas; Yu, Andy; Chang, Bliss; Yeri, Ashish; Li, Haobo; Hobson, Ryan; Lerchenmüller, Carolin; Vujic, Ana; Chaudhari, Vinita; Damilano, Federico; Platt, Colin; et al.
Abstract: Heart failure with preserved ejection fraction (HFpEF) is the most common type of HF in older adults. Although no pharmacological therapy has yet improved survival in HFpEF, exercise training (ExT) has emerged as the most effective intervention to improving functional outcomes in this age‐related disease. The molecular mechanisms by which ExT induces its beneficial effects in HFpEF, however, remain largely unknown. Given the strong association between aging and HFpEF, we hypothesized that ExT might reverse cardiac aging phenotypes that contribute to HFpEF pathophysiology and additionally provide a platform for novel mechanistic and therapeutic discovery. Here, we show that aged (24–30 months) C57BL/6 male mice recapitulate many of the hallmark features of HFpEF, including preserved left ventricular ejection fraction, subclinical systolic dysfunction, diastolic dysfunction, impaired cardiac reserves, exercise intolerance, and pathologic cardiac hypertrophy. Similar to older humans, ExT in old mice improved exercise capacity, diastolic function, and contractile reserves, while reducing pulmonary congestion. Interestingly, RNAseq of explanted hearts showed that ExT did not significantly modulate biological pathways targeted by conventional HF medications. However, it reversed multiple age‐related pathways, including the global downregulation of cell cycle pathways seen in aged hearts, which was associated with increased capillary density, but no effects on cardiac mass or fibrosis. Taken together, these data demonstrate that the aged C57BL/6 male mouse is a valuable model for studying the role of aging biology in HFpEF pathophysiology, and provide a molecular framework for how ExT potentially reverses cardiac aging phenotypes in HFpEF. Abstract : Heart failure with preserved ejection fraction (HFpEF) is the most common type of heart failure in older adults, but has no effective pharmacological therapies. This study shows that exercise training can reverse cardiac aging biology and phenotypes that contribute to HFpEF, and identifies cell cycle pathways as potential novel therapeutic targets for age‐related HFpEF.